2011
DOI: 10.1007/s00442-011-2017-x
|View full text |Cite
|
Sign up to set email alerts
|

Host resistance elicited by methyl jasmonate reduces emission of aggregation pheromones by the spruce bark beetle, Ips typographus

Abstract: We treated Norway spruce (Picea abies) stems with methyl jasmonate (MeJA) to determine possible quantitative and qualitative effects of induced tree defenses on pheromone emission by the spruce bark beetle Ips typographus. We measured the amounts of 2-methyl-3-buten-2-ol and (S)-cis-verbenol, the two main components of the beetle's aggregation pheromone, released from beetle entrance holes, along with phloem terpene content and beetle performance in MeJA-treated and untreated Norway spruce logs. As expected, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
7
24
0
Order By: Relevance
“…Furthermore, we suspect that differences in secondary compounds remaining in the cut bolts can still affect pheromone production by beetles (i.e. Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we suspect that differences in secondary compounds remaining in the cut bolts can still affect pheromone production by beetles (i.e. Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that the profile of volatiles from cut bolts differs to some extent from those emitted from standing live trees. Nevertheless, we suspect that differences in secondary compounds remaining in the cut bolts still can affect pheromone productions by beetles (i.e., Zhao et al 2011) Second, compared to the wide natural range of jack pine forests throughout North America, we sampled trees from relatively few locations. Our most recent work using needles from 610 jack pine trees (or 61 populations) across Canada and the USA demonstrate that jack pine trees show various chemotypes, suggesting that this will likely affect the amount of pheromones, particularly trans-verbenol produced by D. ponderosae (Taft et al 2015).…”
Section: Enantiomeric Composition and Pheromonesmentioning
confidence: 99%
“…Previous studies of the spruce bark beetle and other tree-killing bark beetles have shown that the beetles tend to avoid trees with very strong or rapid terpene accumulation (Boone et al 2011;Schiebe et al 2012;Zhao et al 2011a). Norway spruce had higher total induced terpene concentrations than Sitka and Lutz spruce (55% and 102% higher, respectively), suggesting that the novel hosts should be a more favorable substrate for the spruce bark beetle than Norway spruce.…”
Section: Induced Terpenoid Chemistry and Host Suitabilitymentioning
confidence: 87%
“…In fact, thunbergol and thunbergene were not detected at all in Sitka spruce (Figure 3). The effect of thunbergene and α-longipinene on the spruce bark beetle is unknown, but thunbergol has been suggested to inhibit growth of the beetle's fungal associate E. polonica (Zhao et al 2011a;Zhao et al 2010). Considering the negative effects of thunbergol we were surprised to find a positive relationship between constitutive levels of thunbergol and offspring production.…”
Section: Induced Terpenoid Chemistry and Host Suitabilitymentioning
confidence: 99%